2015
DOI: 10.1038/npjparkd.2015.2
|View full text |Cite
|
Sign up to set email alerts
|

Common genetic variant association with altered HLA expression, synergy with pyrethroid exposure, and risk for Parkinson’s disease: an observational and case–control study

Abstract: Background/Objectives The common non-coding single nucleotide polymorphism (SNP) rs3129882 in HLA-DRA is associated with risk for idiopathic Parkinson’s disease (PD). The location of the SNP in the major histocompatibility complex class II (MHC-II) locus implicates regulation of antigen presentation as a potential mechanism by which immune responses link genetic susceptibility to environmental factors in conferring lifetime risk for PD. Methods For immunophenotyping, blood cells from 81 subjects were analyze… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
78
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(85 citation statements)
references
References 49 publications
5
78
0
2
Order By: Relevance
“…45 . Briefly, PBMCs were isolated from whole blood using density centrifugation with Ficoll-Paque (GE Healthcare, Uppsala, Sweden).…”
Section: Methodsmentioning
confidence: 99%
“…45 . Briefly, PBMCs were isolated from whole blood using density centrifugation with Ficoll-Paque (GE Healthcare, Uppsala, Sweden).…”
Section: Methodsmentioning
confidence: 99%
“…Recognition of an important role of neuroinflammation in human PD and in the α-syn PFF model has been growing. 66,[87][88][89][90][91][92][93][94][95] In addition, previous results demonstrated that dieldrin exposure exacerbates MPTP-induced increases in expression of glial fibrillary acidic protein (GFAP) levels in the striatum, suggesting that dieldrin exposure leads to a greater neuroinflammatory response to a second insult. While we were unable to test expression of neuroinflammatory genes after the application of PFFs, we did identify dieldrin-induced changes in the expression of neuroinflammatory genes.…”
Section: Dieldrin Induced Sex-specific Effects In the Nigrostriatal Pmentioning
confidence: 99%
“…Additionally, there are several hits at the HLA (human leukocyte antigen) locus (Chang et al 2017; Nalls et al 2014) which encodes the major histocompatibility complex class II (MHC-II). Although the association between PD and the HLA region is complex, it has been suggested that the hits at HLA-DRB6 and HLA-DQA1 could implicate regulation of antigen presentation as a potential mechanism by which the immune response links environmental factors to genetic susceptibility in conferring risk for PD (Kannarkat et al 2015). Indeed, Sulzer et al have recently reported that α -synuclein-derived fragments act as antigenic epitopes displayed by HLA receptors, where both helper and cytotoxic T-cell responses are present in a high percentage of patients when tested (Sulzer et al 2017).…”
Section: A Glimpse Into Much Larger Networkmentioning
confidence: 99%